Investigation on water and fertilizer retention properties of hydrated sulphoaluminate cement pastes modified by bentonite for porous ecological concrete - Weichao Li; Qiyong Zhang; Laibo Li; Yali Li; Haiming Zhang; Lingchao Lu (Case Studies in Construction Materials, 2023)
Porous ecological concrete (PEC) consisted of coarse aggregate and hydrated sulphoaluminate cement (SAC) covering on the aggregate is an excellent material for ensuring the safety and protecting the environment of slopes along motorways and river banks. However, the water and fertilizer retention of the PEC cannot meet grass growing demand, which pose a great challenge for the application of PEC. Due to the hydrated SAC directly determined the water absorption and water/fertilizer retention properties of PEC, bentonite was utilized to partially displace SAC for enhancing the water and fertilizer retention of hydrated SAC with the aim of improving the growth environment of the grass planting in the PEC. The influences of bentonite on the water and fertilizer retention properties and basic physic-chemical performance of SAC were studied. The results showed that the optimum replacement level of SAC by bentonite was 2% by mass for improving the water and fertilizer retention of the hardened SAC pastes. In this case, the water and fertilizer retention of hydrated SAC pastes improved by 11.7% and 12.8%, which was beneficial for the growth of grass. In addition, the water absorption ratio of the pastes enhanced 20.6% while the pH of pore solution of the pastes reduced by 0.47 to a value of 10.93. Furthermore, the 1- and 3-day compressive strength of SAC with 2% bentonite reached up to 39.3 MPa and 47.0 MPa, which was slightly higher than that of the reference mix.